Effects of second injection timing on combustion characteristics of the spark ignition direct injection gasoline engines with dimethyl ether enrichment in the intake port. (1st August 2019) - Shi, Lei; Ji, Changwei; Wang, Shuofeng; Su, Teng; Cong, Xiaoyu; Wang, Du; Tang, Chuanqi
Abstract: Dimethyl ether (DME), as a sustainable fuel, could be used as an ignition improver in spark ignition engines to improve the performance under lean conditions. Direct injection engines could gain higher thermal efficiency than the port fuel injection engines. To study the effects of second injection (SOI2) timing on the engine combustion characteristics, experiments were conducted on an engine with independent DME port injection and gasoline direct injection systems. Tests were performed at a constant engine speed of 1400 rpm and manifolds absolute pressure of 60 kPa under excess air ratios of 1.2 and 1.3. The start of injection during intake was kept constant at 300 o CA BTDC and the SOI2 timing was varied from 90 to 150 o CA BTDC. Split injection ratio was 1:1. Results showed that a higher brake thermal efficiency (BTE), lower cyclic variation, HC and particle emissions were obtained for DME-gasoline blends engines. Moreover, the ideal SOI2 timing could make the heat release more concentrated and ease the cyclic variation, which enhance BTE and reduce HC, NOx and particle number emissions. In addition, when more fuel was obtained, the combustion temperature was increased, improving BTE and reducing HC emissions under lean combustion conditions. Highlights: The co-effect of second injection timing and DME addition on GDI engines is studied. Cooperating DME with proper second injection timing improves brake thermal efficiency. Particle number emissions of the gasoline engine are reduced after DME addition.